324 A METABOLOMIC ANALYSIS OF VERY LONG CHAIN FATTY ACID SYNTHESIS IN CONTROL AND REFSUM FIBROBLASTS. (1st January 2005) - Wong, D.; Bassilian, S.; Lim, S.; Lee, W.N. P.
Abstract : Purpose: Inborn errors of peroxisomal metabolism such as Refsum disease (phytanic acid oxidase deficiency) often affect very long chain fatty acid ("VLCFA") synthesis and degradation. Recent advances in metabolomic analysis make it possible to investigate the network of pathways involved in VLCFA metabolism, and to characterize the derangements of these pathways resulting from peroxisomal disorders. Methods: Cell cultures of normal, Refsum disease, and infantile Refsum disease human fibroblasts were enriched with medium containing 0.5 mM universally labeled 13C-stearate every 24 hours for a total incubation of 72 hours. Saturated fatty acids from C16:0 to C24:0 were extracted from saponified cells and were analyzed by gas chromatography/mass spectrometry. Mass isotopomer distribution analysis was performed to determine fatty acid chain elongation. Mathematica® software was used to for mathematical modeling and compartmental analysis. Results/Conclusions: Refsum disease fibroblasts had higher enrichment of the very long chain fatty acids C20:0, C22:0, and C24:0. Using our previously described model (JBC 279: 41302-41309, 2004), we concluded that peroxisomal chain shortening of stearate was increased in Refsum disease and that defects in peroxisomal alpha oxidation may have effects on peroxisomal beta oxidation. Using compartmental analysis, we showed that fibroblasts have two major enzyme systems which are responsible for chain elongation of C18:0 to longer saturated fatty acids. The first is closely linked to peroxisomal chain shortening, and is responsible for generating approximately 90% of the C20:0 synthesized from added C18:0. This enzyme system uses a highly labeled acetyl-CoA pool (most likely peroxisomal) which has greater acetyl-CoA enrichment in Refsum fibroblasts (78%) than in normal fibroblasts (56%). The second system is responsible for generating approximately 70% of the C22:0 and 85% of the C24:0 synthesized from added C18:0. This system uses a lower enrichment acetyl-CoA pool (20-23%) which is unaffected by Refsum disease. Both normal and Refsum fibroblast data are consistent with a model in which fatty acid oxidation and synthesis enzymes are highly compartmentalized. Infantile Refsum cells do not fit this model, consistent with the disruption of compartments due to peroxisomal biogenesis defects. This mathematical approach to metabolomic analysis is equally applicable to other diseases and to animal models, and may be used to extend our knowledge of both normal and abnormal VLCFA metabolism.